Divorce and democracy : a history of personal law in post-independence India / Saumya Saxena. - Saxena, Saumya (Cambridge University Press, 2022)
This book captures the Indian state's difficult dialogue with divorce, mediated largely through religion. By mapping the trajectories of marriage and divorce laws of Hindu, Muslim, and Christian communities in post-colonial India, it explores the dynamic interplay between law, religion, family, minority rights and gender in Indian politics. It demonstrates that the binary frameworks of the private-public divide, individuals versus group rights, and universal rights versus legal pluralism collapse before the peculiarities of religious personal law. Historicizing the legislative and judicial response to decades of public debates and activism on the question of personal law, it suggests that the sustained negotiations over family life within and across the legal landscape provoked a unique and deeply contextual evolution of both, secularism and religion in India's constitutional order. Personal law, therefore, played a key role in defining the place of religion and determining the content of secularism in India's democracy.